1999
DOI: 10.1111/j.1540-8159.1999.tb00623.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality‐of‐Life Six Months After CABG Surgery in Patients Randomized to ICD Versus No ICD Therapy: Findings from the CABG Patch Trial

Abstract: Strategies aimed at easing patients' adjustment to ICDs should be developed and tested for efficacy in the setting of ICD prophylaxis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
94
2
5

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(101 citation statements)
references
References 13 publications
0
94
2
5
Order By: Relevance
“…The Coronary Artery Bypass Graft (CABG) Patch Trial examined the value of prophylactic ICD implantation in patients undergoing coronary artery bypass graft surgery (CABG) (n = 262) versus no ICD (n = 228) after CABG surgery. 22 Mental and physical QOL scores for the patients with ICDs were significantly worse compared with those for patients without ICDs. However, further analyses revealed that there was no difference in QOL for nonshocked patients with ICDs versus those with no ICDs.…”
Section: Psychological Adjustment and The Experience Of Shockmentioning
confidence: 85%
“…The Coronary Artery Bypass Graft (CABG) Patch Trial examined the value of prophylactic ICD implantation in patients undergoing coronary artery bypass graft surgery (CABG) (n = 262) versus no ICD (n = 228) after CABG surgery. 22 Mental and physical QOL scores for the patients with ICDs were significantly worse compared with those for patients without ICDs. However, further analyses revealed that there was no difference in QOL for nonshocked patients with ICDs versus those with no ICDs.…”
Section: Psychological Adjustment and The Experience Of Shockmentioning
confidence: 85%
“…[1][2][3][4][5] Despite differences in the literature between study designs and clinical outcomes, the negative impact of ICD shocks on QoL was consistent between studies and was related to the increased number of shocks received. 3,4 However, whether reduction of shocks by applying ATP therapy improves QoL has not been tested previously. This is the first trial to demonstrate that ATP does improve QoL compared with shock delivery in patients who experience FVT.…”
Section: Discussionmentioning
confidence: 99%
“…Although ICDs are well tolerated by most patients, reports of clinically significant anxiety and depression are common. 1,2 ICD patients receiving shocks exhibit a decline in quality of life (QoL), 3,4 although this finding is not universal. 5 The principal merit of ATP from the patient's perspective is the avoidance of painful shocks.…”
mentioning
confidence: 99%
“…Analiza QoL była celem substudy tego badania (490 pacjentów 228 z ICD i 262 bez ICD) [21]. Jakość życia, za pomocą SF-36, oceniano 6 miesięcy po zabiegu pomostowania aortalno-wieńcowego (CABG, coronary artery by-pass grafting).…”
Section: Badanie Cabg-patchunclassified